Wireless and Simultaneous Detections of Multiple Bio-Molecules in a Single Sensor Using Love Wave Biosensor - Oh, Haekwan (Sensors (Basel), 2014)
A Love wave-based biosensor with a 440 MHz center frequency was developed for the simultaneous detection of two different analytes of Cartilage Oligomeric Matrix Protein (COMP) and rabbit immunoglobulin G (IgG) in a single sensor. The developed biosensor consists of one-port surface acoustic wave (SAW) reflective delay lines on a 41° YX LiNbO(3) piezoelectric substrate, a poly(methyl methacrylate) (PMMA) waveguide layer, and two different sensitive films. The Love wave biosensor was wirelessly characterized using two antennas and a network analyzer. The binding of the analytes to the sensitive layers induced a large change in the time positions of the original reflection peaks mainly due to the mass loading effect. The assessed time shifts in the reflection peaks were matched well with the predicted values from coupling of mode (COM) modeling. The sensitivities evaluated from the sensitive films were ∼15 deg/μg/mL for the rabbit IgG and ∼1.8 deg/ng/mL for COMP.